PERAN SERTA MASYARAKAT DESA HUTAN DALAM MENDUKUNG KEGIATAN PENYULUHANKEHUTANAN DI DESA TUNGGUL BOYOK - Wodon, Friadi Indra; Muin, Sudirman; AM, Iskandar (Universitas Tanjungpura, 2013)
The purpose of this study was to look atthe role of forest village communities in supporting activity counseling and see whether there is a relationship between the factors Age, Education Level, Income Level, Now settled long, Total Family Dependents people's perception of counselor behavior and the behavior of the Cosmopolitan field extension with the participation of forest villagers in support of forestry extension. Data analysis in research using descriptive analysis and inferential analysis of data obtained from field observations (primary data) are grouped into data in the form of quantitative and qualitative data in the form is done as it is, while the data is transformed into the form qualitative in quantitative form using a Likert Scale. Based on the analysis that had been done, it can be drawn some conclusions as follows Characteristics of community participation in the Village Wait Boyok showed high terhapa forestry extensionThere was no significant relationship between age, education level, number of dependents, income level, with the participation of the community in support of forestry extension in the Village Wait Tunggul Boyok.There are significant relationship between long settled factors, the level of perception and cosmopolitan with community participation in support of forestry extension in the village Tunggul Boyok Key Words : Role and also society, forest countryside,counselling of forestry